Analysis of a Drosophila tRNA gene cluster: two tRNA[leu] genes contain intervening sequences. - Robinson, R.R.; Davidson, N. (Cell, 1981)
A recombinant DNA phage containing a cluster of Drosophila melanogaster tRNA genes has been isolated and analyzed. The insert of this phage has been mapped by in situ hybridization to chromosomal region 50AB, a known tRNA site. Nucleotide sequencing of the entire Drosophila tRNA coding region reveals seven tRNA genes spanning 2.5 kb of chromosomal DNA. This cluster is separated from other tRNA regions on the chromosome by at least 2.7 kb on one side, and 9.6 kb on the other. Two tRNA genes are nearly identical and contain intervening sequences of length 38 and 45 bases, respectively, in the anticodon loop. These two genes are assigned to be tRNALeu genes because of significant sequence homology with yeast tRNA3Leu, and secondary structure homology with yeast tRNA3Leu intervening sequence. In addition, an 8 base sequence (AAAAUCUU) is conserved in the same location in the intervening sequences of Drosophila tRNALeu genes and a yeast tRNA3Leu gene. Similar sequenes occur in all other tRNAs containing intervening sequences. The remaining five genes are identical tRNAIle genes, which are also identical to a tRNAIle gene from chromosomal region 42A. The 5' flanking regions are only weakly homologous, but each set of isoacceptors contains short regions of strong homology approximately 20 nucleotides preceding the tRNA coding sequences: GCNTTTTG preceding tRNAIle genes; and GANTTTGG preceding tRNALeu genes. The genes are irregularly distributed on both DNA strands; spacing regions are divergent in sequence and length.